Plan Identification of Community Care Fire at Holcim Educational Forest Cibadak Sukabumi PEMBENTUKAN MASYARAKAT PEDULI API SEBAGAI STRATEGI PENGENDALIAN KEBAKARAN HUTAN DI HUTAN PENDIDIKAN HOLCIM CIBADAK SUKABUMI - Bambang Hero Saharjo; Muhammad Ikbal Putera (Jurnal Silvikultur Tropika, 2015)
Holcim Educational Forest Cibadak is an ex-mining land of silica sand PT. Holcim Indonesia which recently cooperates with Faculty of Forestry Bogor Agricultural University in order to create educational forest. Community Care Fire is a well trained community which is willingly care toward forest fires and land control (Dephut 2009). The purposes of this research are to analyze community’s respond and decision toward establishment of Community Care Fire also to collect community’s participation data toward Community Care Fire establishment. The result of this research indicates that positive respond is got that for about 47 respondents or 67.14% of 70 respondents declared that they are willing to participate in Community Care Fire establishment. The reason for their participation might be caused that the community have a high value of environmental awareness and desire to cooperate with Holcim Educational Forest Cibadak, thereby it may become an appropriate long term program recommendation toward people empowerment.Key words: Community Care Fire, Community’s participation, forest fires control effort, Holcim Educational Forest Cibadak